TRANSFORMING COMMERCE IN DEVELOPING ECONOMIES THROUGH E-BUSINESS ADOPTION AND SUSTAINABLE DIGITAL INTEGRATION - Yusof, Mohamed Suhaimi; Abdul Razak, Nurshuhaida (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The rapid expansion of e-business has reshaped global commerce and has had especially significant effects within developing economies. This paper examines the evolving e-business landscape across emerging markets and explores the balance between expanding opportunities and persistent structural challenges. Digital platforms, mobile banking, and cloud-based services are among the main drivers enabling firms to broaden market access and strengthen competitiveness. However, adoption is frequently constrained by weak technological infrastructure, limited organizational readiness, regulatory uncertainty, cybersecurity vulnerabilities, and inefficiencies in logistics systems. Differences in digital access, managerial skills, and levels of trust strongly influence the ability of businesses and individuals to participate in digital markets. In addition, policy environments and regulatory frameworks can either support or restrict the advancement of e-business activities. Issues of inclusivity, such as gender-related gaps and inequalities between rural and urban regions, further highlight the uneven distribution of benefits from digital transformation. Although emerging technologies such as artificial intelligence, blockchain, and the Internet of Things have the potential to enhance efficiency and transparency, their implementation remains limited across many developing regions. Building resilient and inclusive e-business ecosystems therefore requires coordinated strategies that include investment in infrastructure, development of digital capabilities, establishment of trust and security mechanisms, regulatory improvement, and the strengthening of logistics networks. By addressing these interconnected challenges, developing economies can better position e-business as a driver of sustainable growth, global integration, and equitable development.